Emotions, Planning and Co-production: Distrust, Anger and Fear at Participatory Boundaries in Bengaluru. (November 2020) - Sundaresan, Jayaraj; John, Benjamin
Emotions relationally and performatively constitute the very boundaries that distinguish the subject from the other(s). The urban human in India is affectively constituted by many intense emotional experiences of everyday life. Adopting a participation view of planning and drawing from Sarah Ahmed (2014, The cultural politics of emotion . Edinburgh University Press), we examine 'what emotions do' in the planning and participatory atmospheres (Buser, 2014, Planning Theory, vol. 13, pp. 227–243) in Bangalore. Tracing emotional content embedded in participations and non-participations, we demonstrate how distrust, anger and fear co-produced the process and outcomes of the 2031 Master Plan of Bangalore. We join the few emerging scholars that call attention to the emotional geographies of planning, particularly to be able to transform the continuing colonial urban management practice in the postcolonial world to that of planning. Planning, we argue, has to involve participation, in which emotions, we demonstrate, are the connective tissue (Newman, 2012, Critical Policy Studies, vol. 6, pp. 465–479).